2010
DOI: 10.7863/jum.2010.29.12.1717
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings for the Common Extensor Tendon of the Elbow in the General Population

Abstract: Objective. To describe structural characteristics and sonographic alterations of the common extensor tendon (CET). Methods. In 240 patients, we determined the body mass index; sonographic CET thickness, morphologic characteristics, and alterations; and color Doppler measurements of the epicondylar artery width and peak systolic velocity. Age, sex, epicondylalgia history, activities (work, sports, and hobbies), and dominant and nondominant elbows were noted. . Thickness correlated weakly with age (dominant, r =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
5
30
1
Order By: Relevance
“…5,13 However, the common extensor tendon is thicker in patients with a history of epicondylalgia, and its size is associated with the patient's weight. 22 Smoking may interfere with circulation to tendons by slowing their healing and thus may result in lateral epicondylitis. 13 However, another study reported no such association.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 However, the common extensor tendon is thicker in patients with a history of epicondylalgia, and its size is associated with the patient's weight. 22 Smoking may interfere with circulation to tendons by slowing their healing and thus may result in lateral epicondylitis. 13 However, another study reported no such association.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the term ‘Lateral epicondylalgia’ is irrelevant to the nature, acuity and sources of pathology of lateral elbow symptoms [9], the name ‘Lateral epicondylalgia’ encompasses lateral epicondylitis [10], lateral elbow tendinosis [11], lateral elbow enthesopathy [12,13], or lateral elbow epicondylopathy [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite using MSUS imaging to assess for changes within the tendon in all participants in Chapters 8 and 9, we decided not to include the results of the MSUS examination as part of the inclusion criteria but include participants into the study based on the results of a clinical diagnosis using a standardised clinical examination, in line with previous major randomised controlled trials (Bisset et al, 2006a;Coombes, Bisset, Brooks, Khan, & Vicenzino, 2013). Although MSUS imaging identifies the presence or absence of greyscale features and neovascularisation within the tendon, results of Study 3 (see Chapter 7) and evidence from others has shown a high percentage of individuals with no history of pain, trauma, or treatment have tendon changes visible with MSUS imaging (Cook et al, 1998;Fredberg & Bolvig, 2002;Giombini et al, 2013;Heales et al, 2014a;Jaén-Díaz et al, 2010;Ustuner et al, 2013). Finally, due to the case-control study design implemented within this thesis it is not possible to determine whether differences in the motor system are associated with the cause or as a consequence of LE.…”
Section: Research Design Featuresmentioning
confidence: 63%
“…Tendon pathology of the common extensor origin in 12 to 13% of asymptomatic individuals has been validated with musculoskeletal ultrasound imaging, and this is greater in the dominant arm and with increasing age (Jaén-Díaz et al, 2010;Ustuner, Toprak, Baskan, & Oztuna, 2013). Jaén-Díaz and colleagues (Jaén-Díaz et al, 2010) revealed that 85% of individuals with asymptomatic tendon pathology were older than 40 years of age. In the current study 29 (91%) of the 32 pain-free controls were 40 or more years of age, which might explain the high proportion of tendon abnormality.…”
Section: Tendon Pathology In Healthy Controlsmentioning
confidence: 99%
See 1 more Smart Citation